Understanding COVID-19 dynamics and the effects of interventions in the Philippines: A mathematical modelling study - Jamie M. Caldwell, PhD; Elvira de Lara-Tuprio, PhD; Timothy Robin Teng, PhD; Maria Regina Justina E. Estuar, PhD; Raymond Francis R. Sarmiento, MD; Milinda Abayawardana, B.Eng; Robert Neil F. Leong, MS; Richard T. Gray, PhD; James G. Wood, PhD; Linh-Vi Le; Emma S. McBryde, PhD; Romain Ragonnet, PhD; et al. (Elsevier, 2021)
ABSTRACT: Background: COVID-19 initially caused less severe outbreaks in many low- and middle-income countries (LMIC) compared with many high-income countries, possibly because of differing demographics, socioeconomics, surveillance, and policy responses. Here, we investigate the role of multiple factors on COVID-19 dynamics in the Philippines, a LMIC that has had a relatively severe COVID-19 outbreak. Methods: We applied an age-structured compartmental model that incorporated time-varying mobility, testing, and personal protective behaviors (through a "Minimum Health Standards" policy, MHS) to represent the first wave of the Philippines COVID-19 epidemic nationally and for three highly affected regions (Calabarzon, Central Visayas, and the National Capital Region). We estimated effects of control measures, key epidemiological parameters, and interventions. Findings: Population age structure, contact rates, mobility, testing, and MHS were sufficient to explain the Philippines epidemic based on the good fit between modelled and reported cases, hospitalisations, and deaths. The model indicated that MHS reduced the probability of transmission per contact by 13-27%. The February 2021 case detection rate was estimated at ~8%, population recovered at ~9%, and scenario projections indicated high sensitivity to MHS adherence. Interpretation: COVID-19 dynamics in the Philippines are driven by age, contact structure, mobility, and MHS adherence. Continued compliance with low-cost MHS should help the Philippines control the epidemic until vaccines are widely distributed, but disease resurgence may be occurring due to a combination of low population immunity and detection rates and new variants of concern.